PENGARUH LITERASI KEUANGAN SYARIAH, GAYA HIDUP HEDONISME, DAN PINJAMAN ONLINE TERHADAP PERILAKU KONSUMTIF GEN Z KOTA BANDAR LAMPUNG - Ferdi, Muhammmad Tri Ferdiansyah; Any, Any Eliza; Ujang, Ujang Hanief Musthofa (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2026)
This study examines the influence of Islamic financial literacy, hedonistic lifestyle, and online loans on the consumptive behavior of Generation Z in Bandar Lampung City. The background of the problem stems from Gen Z's high consumptive tendencies due to digital exposure, low Islamic financial literacy, and easy access to online loans that trigger impulsive purchases. This research aims to analyze the simultaneous and partial influence of these three variables on consumptive behavior and examine consumptive behavior from an Islamic economic perspective. The research method employs a quantitative approach with purposive and accidental sampling techniques involving 100 Gen Z respondents aged 17-24 years. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS 26. The results indicate that simultaneously, Islamic financial literacy, hedonistic lifestyle, and online loans significantly influence consumptive behavior F=11.953. Partially, hedonistic lifestyle t=5.131 and online loans t=3.002 have significant positive effects, while Islamic financial literacy t=-1.039 has no significant effect. The Adjusted R² value of 0.249 indicates that the three variables explain 24.9% of the variation in consumptive behavior. From an Islamic economic perspective, Gen Z's consumptive behavior should be directed toward proportional, halal consumption while avoiding israf and tabdzir in accordance with sharia principles. Keywords: Islamic Financial Literacy, Hedonistic Lifestyle, Online Loans, Consumptive behavior, Generation Z